BRAF V600E-mutated lung adenocarcinoma with thyroid metastasis as the initial manifestation: a case report - Liu, Yufei; Lei, Hanhan; Cai, Lingling; Tan, Yuyan; Song, Xinyu (Frontiers in Oncology, 2025)
Thyroid metastasis of lung adenocarcinoma is exceedingly uncommon. Here we present a case of a 72-year-old Chinese male with hoarseness, dysphagia, pain, and palpable thyroid nodules. Ultrasonography-guided thyroid fine-needle aspiration cytology (FNAC) suggested a high-grade follicular-derived thyroid carcinoma (HGFCTC). Molecular analysis identified a BRAF V600E mutation. Comprehensive histopathological and immunohistochemical examinations, however, revealed that the thyroid cancer originated from the left lung. The patient received a 6-month post-operative dual-target therapy with dalafenib and trametinib. As of the last follow-up, the patient was still alive, demonstrating the effectiveness of targeted therapy.